In-situ crosslinked lignin additives in tire rubber for minimizing microplastic pollution - Uiseok Hwang; June-Young Chung; Xin Yang; Soochan Kim; Jae-Do Nam (Materials & Design, 2025)
Recently, the emergence of microplastics has become a serious environmental pollution issue. Tire wear particles (TWPs), generated by friction between vehicle tires and road surfaces during driving, are highly toxic and a major source of microplastic emissions. Paradoxically, this issue is further exacerbated by the rapid increase in eco-friendly electric vehicles, which are significantly heavier than traditional internal combustion engine vehicles, leading to greater TWP generation. In this work, we introduce sustainable, lignin-based additives to reduce microplastic pollution caused by TWP generation. When incorporated into tire rubber and in-situ crosslinked with amines, this lignin imparts excellent mechanical properties, thermal stability, and abrasion resistance to the rubber composites. The crosslinking reaction between lignin and amines can accelerate curing and increase crosslink density by up to 43.5 % (5.54 × 10−4 mol/cm3), thereby reducing areas susceptible to abrasion and improving abrasion resistance. Notably, with a 3:1 phr ratio of lignin to amine, the rubber composite exhibits superior anti-abrasion performance, significantly reducing TWP generation by 7.7 % compared to a typical rubber composite after 10,000 abrasion cycles. The newly developed lignin-based rubber composites and methodology hold tremendous potential as a promising solution for next-generation eco-friendly vehicle tires and microplastic reduction.